Pengaruh Aplikasi Trichoderma sp. dan Pupuk Organik Kotoran Ayam Terhadap Pertumbuhan Bawang Merah (Allium Ascolonicum L) - Nurmaini Nababan; Rahmadina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of chicken manure and Trichoderma sp. on the growth and health of shallots (Allium ascalonicum L.). The study was conducted in June–July 2025 at the Greenhouse of the State Islamic University of North Sumatra using a factorial randomized block design (RAK) with two factors. The first factor was the dose of chicken manure (P0 = 0 g, P1 = 100 g, P2 = 120 g, P3 = 140 g), and the second factor was the dose of Trichoderma sp. (T0 = 0 g, T1 = 25 g, T2 = 30 g, T3 = 35 g). The two factors were combined into 16 treatments with three replicates. The parameters observed included plant height, number of leaves, number of wilted leaves, root length, fresh weight, and dry weight of plants. The data were analyzed using ANOVA and followed by DMRT test at the 5% level. The results showed that chicken manure and Trichoderma sp. had a significant effect on plant height, number of leaves, fresh weight, dry weight, and were able to suppress leaf wilting symptoms, but had no significant effect on root length. The combination of treatments yielded the best results compared to single treatments, especially at chicken manure doses P2–P3 and Trichoderma sp. T3. Thus, the application of chicken manure combined with Trichoderma sp. has the potential to optimize shallot growth in an environmentally friendly manner.